Monitoring zagrożenia upadłością banków spółdzielczych z wykorzystaniem metody SWOBS - Zychowicz, Mariusz (Estimating the State of Emergency of Co-Operative Banks to Bankruptcy Using the SWOBS Method, 2005)
The object of the report is to: introduce substantial methods of estimating the state of emergency of banks to bankruptcy, present genesis methods of estimating the state of emergency of Polish co-operative banks of bankruptcy, description of the SWOBS method, use the SWOBS method in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 151-161